2022
DOI: 10.12660/cgpc.v27n86.85574
|View full text |Cite
|
Sign up to set email alerts
|

A política e a economia do governo Bolsonaro: uma análise sobre a captura do orçamento

Abstract: O objetivo deste artigo é analisar o final do governo Bolsonaro do ponto de vista da capacidade de arbitrar o conflito distributivo e de governar. Para tanto, analisa-se o processo orçamentário 2021/2022. A análise é de economia política e de política. Parte-se do suposto de que o orçamento é a expressão dos conflitos distributivos inerentes à sociedade e de que tais conflitos devem ser arbitrados. Do contrário, haverá perda  de agenda e  descontrole da política fiscal. O artigo descreve como elementos institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
3
0
3
Order By: Relevance
“…This study aimed to analyze, according to discussions on public policy instruments and the bibliography on public security policies in Brazil, the profile of the Union voluntary transfers made by MJSP to the various Brazilian subnational entities. It was found that, over the years, the participation of the National Congress in the allocation of budget resources has increased, corroborating the study by M. F. G. Silva and Teixeira (2022), which showed the robust growth of Congress, driven by the phenomenon known as "impositive budget", which allowed the growth of the power to allocate resources through parliamentary amendments. Associated with this, the parliamentary interest in agendas related to public security (Quadros & R. M. Madeira, 2018) is reflected in the signing of agreements.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This study aimed to analyze, according to discussions on public policy instruments and the bibliography on public security policies in Brazil, the profile of the Union voluntary transfers made by MJSP to the various Brazilian subnational entities. It was found that, over the years, the participation of the National Congress in the allocation of budget resources has increased, corroborating the study by M. F. G. Silva and Teixeira (2022), which showed the robust growth of Congress, driven by the phenomenon known as "impositive budget", which allowed the growth of the power to allocate resources through parliamentary amendments. Associated with this, the parliamentary interest in agendas related to public security (Quadros & R. M. Madeira, 2018) is reflected in the signing of agreements.…”
Section: Discussionsupporting
confidence: 76%
“…When it comes to parliamentary amendments, the process is usually the opposite, considering that the congressman first designates the resources to some entity, which then presents a work plan with the objectives and the implementation proposal. Related to this, in recent years, a robust gain in power by the Legislature has been identified, especially regarding the power to allocate resources through parliamentary amendments (M. F. G. Silva & Teixeira, 2022) and the so-called impositive budget.…”
Section: Theoretical Referentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Parliamentary amendments are a way for the legislative power to participate in the budget process, but they have been pointed out as a mechanism of political bargaining between the executive and legislative branches, disconnected from health planning 55,56 . Still, in the specific case of the rapporteur amendments, instituted in 2019 57 , the destination of the resources, as well as the criteria that guide their allocation and the name of the parliamentarian are not made public, which allows us to affirm that a parallel budget has been made official and without transparency, classified as 'secret' , and that it has been used for the purpose of obtaining political support from parliamentarians to consolidate electoral loyalty 57 . Therefore, although the Federal Supreme Court considered the distribution of resources of the rapporteur's amendments in December 2022 unconstitutional, it is important to take into account that SUS resources have been drained in order to finance the 'secret budget' 58 .…”
Section: Discussionmentioning
confidence: 99%
“…As emendas parlamentares são uma forma de o poder legislativo participar do processo orçamentário, contudo têm sido apontadas como mecanismo de barganha política entre os poderes Executivo e Legislativo, desconexa do planejamento sanitário 55,56 . E no caso específico das emendas de relator, instituídas em 2019 57 , o destino dos recursos, bem como os cri-térios que orientam sua alocação e o nome do parlamentar não são públicos, o que permite afirmar que se oficializou um orçamento paralelo e sem transparência, classificado como "secreto", e que têm sido utilizadas com a finalidade de obter apoio político dos parlamentares para consolidar a fidelidade eleitoral 57 . Assim, embora o Supremo Tribunal Federal tenha considerado inconstitucional a distribuição de recursos das emendas de relator em dezembro de 2022, é preocupante constatar que os recursos do SUS tenham sido drenados para financiar o "orçamento secreto" 58 .…”
Section: Valor Pago Anual Per Capita (R$)unclassified